Project management in higher education: a grounded theory case study. Issue 5 (28th February 2019) - Porter, Seth
Abstract : Purpose: This paper analyzes project and portfolio management within a major research library, while it was undergoing a complete physical renovation and reinvention of programs and services. This is a complex, almost 100-million-dollar undertaking that implemented a project management (PM) methodology known as portfolio management. The purpose of this paper is to analyze the implementation and management of this process and provide a brief overview on project and portfolio management as a discipline. Additionally, it provides strengths and weaknesses as well as recommendations when implementing PM. Design/methodology/approach: The analysis uses a qualitative research methodology case study with a theoretical foundation of inductive grounded theory. The case study is based primarily on seven interviews of project managers who are involved with the project. It also uses document analysis to assist in triangulating the findings and provide a contextual overview of a complex process. A number of themes emerged into overall categories and findings. Findings: The key takeaways were the perceived strengths and weaknesses of the process. The strengths were improved communication and transparency, improved organization and documentation and formal decision-making process and resource allocation. The weaknesses were the hammer and the nail problem, the tools and paperwork, rigidity and the lack of agility within the process. This study also describes the process in detail and gives recommendations for improving the methods implemented in similar circumstances. Originality/value: This paper analyzes strategic management concepts from an empirical grounded theory approach and real-world perspective with key recommendations.